A hearth in candlewood : a novel - Parr, Delia (Parr, Delia. Candlewood trilogy, 2006)
The engaging village of Candlewood in 1840s New York provides a glimpse into the past that will inspire and uplift today's readers. Fifty-one-year-old Emma Garrett runs Hill House, a boardinghouse on a hill at the edge of town. Emma ministers to her guests, both the transient and those who call Hill House home. Gifted with an uncanny ability to see the unique strengths of her guests, Emma serves and challenges them with homespun wisdom and absolute faith in God. When eighty-year-old Widow Leonard shows up at Hill House to escape a heated land dispute between her two sons, Emma welcomes her and tries to help her heal the family feud. But tragedy soon hits closer to home when Emma's very ownership of Hill House is called into question!